EFEKTIVITAS KOMPRES JAHE DAN KOMPRES AIR HANGAT TERHADAP INTENSITAS NYERI SENDI PADA LANSIA DI POSYANDU LANSIA (DESA MINOHOREJO KEC. WIDANG KAB. TUBAN) - Qomariah, Siti; Ubaidillah, Moh (Universitas Duta Bangsa Surakarta, 2024)
ABSTRACTJoint pain is a major problem that occurs in the elderly. Joint paint often lead to impaired mobility, independence functions, participation in activities social development, as well as quality of life and is one of the ten mein causes disability in the country is growing. The purpose of this study was to determine the effectiveness of ginger compresses and warm water compresses on the intensity of joint paint in the elderly at Elderly Posyandu (Minohorejo Village, Widang District, Tuban Regency).The research method used is quasy-experimental with a